Pemeriksaan Ultrasonografi Elastografi dalam Diagnosis Penyakit Ginjal - Adisti, Fransiska; Ramadhian, Muhammad Ricky; Maulana, Muhammad; Berawi, Khairun Nisa (Medula, 2024)
Ultrasonography (USG) is a diagnostic tool in medical imaging that operates on the principle of ultrasound waves emitted by a transducer. Recent advancements in USG technology have significantly enhanced its diagnostic capabilities. Renal elastography, a specialized application, enables the assessment of tissue stiffness or elasticity. The technique involves applying pressure to the tissue and measuring the resulting strain, providing valuable insights into the extent of fibrosis in the renal parenchyma. This article presents a comprehensive review of renal elastography ultrasonography and its clinical applications. USG is a non-invasive imaging modality that requires no special preparation, typically performed with the patient in a supine position. The kidneys are evaluated in longitudinal and transverse planes using a transducer positioned at the flank. Various elastography techniques exist, categorized based on the intensity of external pressure applied.